AGAMA DALAM DIMENSI POLITIK DAN SPIRITUALITAS Analisa Isi Posting, Caption dan Interaksi dalam Akun @persatuan_pribumi - Atika Ulfia Adlina (Jurnal SMART (Studi Masyarakat, Religi, dan Tradisi), 2018)
This research is about to analyze the contents of messages posted by instagram @persatuan_pribumi account. This research uses qualitative descriptive approach with constructivism paradigm and with netnography method. This study aims to understand the extent to which these accounts and their interactions speak about religion and politics as well as how the spirituality is owned by the account. Religion ridden by political interests, poorly intellectual, emotionally embodied comments in spirituality, proves that it takes serious effort from all walks of life to sterilize social media from negative content. This research also provides an understanding of what is actually happening in the instagram of @persatuan_pribumi account when they talk about religion and politics.